Legal Security in Iraq: Commercial and administrative law is a model - پڕۆفسیۆرى یاریدەدەر دکتۆر سەنگەر داوود محمد; مامۆستاى یاریدەدەر عەلى تاهە ئەکرەم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This research deals with legal security, which is one of the most important elements of a legal state based on the rule of law. This leads the public authorities to commit themselves to ensuring some degree of stability in legal relations and a minimum level of stability for the legal centers, so that individuals can act with confidence in the guidance of the legal rules and regulations that are in place and arrange their conditions without being subjected to sudden actions that undermine their legitimate expectations and destabilize their legal status; as an individual can only obtain his or her legitimate rights under established and stable legal system in all areas. The existence of some kind of relative stability in legal relations reinforces the stability of legal centers and promotes peace and tranquility and achieves human security in its broad dimensions. In contrast, the instability and disorder of laws create chaos, sedition and the disruption of the normal lives of individuals, thereby compromising the sovereignty and prestige of the state. To this end, it is necessary to look for the elements that stabilize legal rules in a manner that guarantees the fundamental rights and freedoms of individuals under state sovereignty and law. The appropriateness of the law to society is measured by the extent to which the law responds to the requirements and needs of the society. The more the rule of law is accepted by the addressees, the more realistic it is and the better it will be in practice. However, reaching that aim cannot be achieved in the absence of a clear and predictable legislative vision. Respect for the legal rule is the result of respect for a sound and stable legal and judicial environment. The quality of the drafting and the legal text must be clear, easy to understand and precise in determining the requirements. In view of the forgoing, the research entitled "Legal Security in Iraq - Commercial and Administrative Law" is a serious scientific effort to present the concept of legal security and the dimensions of its relationship with justice, the rule of law, stability and tranquility in society, and to indicate the gaps, shortcomings, shortcomings and legal contradictions in which the Iraqi legislators of commercial and administrative law have made, in order to address them and to identify appropriate suggestions and proposals to reduce them.